Effect of Scanning Acceleration on the Leakage Signal in Magnetic Flux Leakage Type of Non-destructive Testing - Lintao Zhang (Journal of Nondestructive Evaluation, 2023)
This work investigates the influence of acceleration on the leakage signal in magnetic flux leakage type of non-destructive testing. The research is addressed through both designed experiments and simulations. The results showed that the leakage signal, represented by using peak to peak value, decreases between 15.1% and 26.6% under acceleration. The simulation results indicated that the main reason for the decrease is due to the difference in the distortion of the magnetic field for cases with and without acceleration, which is the result of the different eddy current distributions in the specimen. The findings will help to allow the optimisation of a magnetic flux leakage system to ensure that main defect features can be measured more accurately during the machine acceleration phase of scanning. It also shows the importance of conducting measurements at constant velocity, wherever possible.